2007
DOI: 10.1016/j.specom.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Language-dependent state clustering for multilingual acoustic modelling

Abstract: The development of automatic speech recognition systems requires significant quantities of annotated acoustic data. In South Africa, the large number of spoken languages hampers such data collection efforts. Furthermore, code switching and mixing are commonplace since most citizens speak two or more languages fluently. As a result a considerable degree of phonetic cross pollination between languages can be expected. We investigate whether it is possible to combine speech data from different languages in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 14 publications
0
25
0
Order By: Relevance
“…Usually, a language with large amounts of training data is used to simulate small amounts of target training data (Imseng et al, 2012a;Qian et al, 2011). For instance (Niesler, 2007) studied the sharing of resources on real underresourced languages, including Afrikaans, inspired by multilingual acoustic modeling techniques proposed by Schultz and Waibel (2001). However, only marginal ASR performance gains were reported.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, a language with large amounts of training data is used to simulate small amounts of target training data (Imseng et al, 2012a;Qian et al, 2011). For instance (Niesler, 2007) studied the sharing of resources on real underresourced languages, including Afrikaans, inspired by multilingual acoustic modeling techniques proposed by Schultz and Waibel (2001). However, only marginal ASR performance gains were reported.…”
Section: Introductionmentioning
confidence: 99%
“…However when multilingual ASR for many languages is desired, data collection and labeling may become too costly that alternative solutions are often desired. One potential solution is to explore shared acoustic phonetic structures among different languages to build a large set of acoustic models (e.g., [1][2] [3][5] [7][8] [9]) that characterize all the phone units needed in order to cover all the spoken languages being considered. This is sometimes called multilingual ASR or cross-lingual ASR when no language-specific data is available to build the acoustic models for the target language.…”
Section: Introductionmentioning
confidence: 99%
“…Both Wheatley et al 1994 andSchultz andWaibel 2001 found that useful gains could be obtained by sharing data across languages with the size of the benefit dependent on the similarity of the sound systems of the languages combined. In the only crosslingual adaptation study using African languages (Niesler 2007), similar gains have not yet been observed.…”
Section: Asr For Resource-scarce Languagesmentioning
confidence: 88%